The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1002/ecs2.2731
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of hydrogeomorphology on fish community structure in a large floodplain river

Abstract: Biocomplexity is an emergent property of ecosystems that captures the interplay of structures and processes at multiple scales. These interactions can establish a dynamic habitat template that serves as a filter to define ecological organization across landscapes. Studies of biocomplexity in floodplain rivers typically focus on hydrological variability or geomorphic heterogeneity separately, with their interactions being an output rather than the direct focus of investigations. This study examines the interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…However, the results of this study align with previous research demonstrating associations between hydrogeomorphic and fish communities in river systems (cf. Boys & Thoms, ; Delong, Thoms, & Sorenson, ). Future studies incorporating more intense sampling of each of the FPZ are recommended to evaluate our hypothesis put forward in this study of Andean river systems.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of this study align with previous research demonstrating associations between hydrogeomorphic and fish communities in river systems (cf. Boys & Thoms, ; Delong, Thoms, & Sorenson, ). Future studies incorporating more intense sampling of each of the FPZ are recommended to evaluate our hypothesis put forward in this study of Andean river systems.…”
Section: Discussionmentioning
confidence: 99%
“…The region of the UMR in this study, in contrast, is an anabranching system with numerous off-channel aquatic habitats, and the 'pool' effect above dams is markedly smaller than that of the LOR (Delong et al, 2019). Greater physical heterogeneity of the UMR is likely the contributing factor in minimizing the influence of hydrology on the trophic status of fish.…”
Section: Discussionmentioning
confidence: 71%
“…Hydrology and geomorphology act directly and indirectly to define the physical and ecological characteristics of riverine landscapes (Thorp et al, 2008). Differential interactions of hydrology and geomorphology establish a template that determines ecological form and function of river ecosystems (Delong, Thoms, & Sorenson, 2019). This dynamic interaction can lead to feedback loops whereby changes in physical characteristics shift ecological structure and/or function to alternate functional states (Dent et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the most recent 8Rs Redux: CARL Human Resources Study, it is reported that "a total of 37% of librarians have earned at least two graduate degrees (MLIS plus 32% with a second Master's degree; 5% with a PhD)." 61 In addition, the survey results reveal that collective agreement language does not necessarily provide librarians the freedom to pursue their own research agenda. There is often consider-able managerial control by supervisors.…”
Section: Definitions Of Research and Scholarshipmentioning
confidence: 98%